2012
DOI: 10.1021/ja3054018
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Greenish Blue Electrochemiluminescence from Fluorene and Spirobifluorene Derivatives

Abstract: The spectroscopic and electrochemical behavior as well as electrogenerated chemiluminescence (ECL) of a series of donor-π-donor derivatives bearing triphenylamine groups as donor connected to a fluorene, 2,7-bis-(4-(N,N-diphenylamino)phen-1-yl)-9,9'-dimethylfluorene (1), or spirobifluorene core, 2,7-bis-(4-(N,N-diphenylamino)phen-1-yl)-9,9'-spirobifluorene (2) and 2,2',7,7'-tetrakis(4-(N,N-diphenylamino)phen-1-yl)-9,9'-spirobifluorene (3), were investigated. Besides a high photoluminescence (PL) quantum yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 49 publications
4
87
0
1
Order By: Relevance
“…By comparison with the corresponding fluorescence spectra, redshifts were observed in ECL spectra (7 nm for 1 and 3 nm for 4 ). Such redshifts are common in ECL and are caused by the inner filter effect due to the high concentration of chromophores used in ECL experiments . Nonetheless, these results confirmed that the same excited state 1 * were produced by photochemical and electrochemical excitation.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…By comparison with the corresponding fluorescence spectra, redshifts were observed in ECL spectra (7 nm for 1 and 3 nm for 4 ). Such redshifts are common in ECL and are caused by the inner filter effect due to the high concentration of chromophores used in ECL experiments . Nonetheless, these results confirmed that the same excited state 1 * were produced by photochemical and electrochemical excitation.…”
Section: Resultssupporting
confidence: 54%
“…This demonstrates a diffusion‐controlled process on the Pt surface in this potential window for all three well‐separated anodic steps. The next two reversible anodic one‐electron waves are consistent with oxidation of the central spirofluorene core . However, another hypothesis that cannot be excluded is that the reversible one‐electron oxidation waves are related to oxidation of the thiophene moieties.…”
Section: Resultsmentioning
confidence: 89%
“…During the past decades, great efforts were focused on the development of novel EL materials. [11][12][13][14][15] Organic molecules with conjugated π-electron systems have been extensively studied and demonstrated as ideal materials for applications in OLEDs in recent years. [16][17][18][19][20] Luminescent properties and charge carrier transporting characteristics of a conjugated molecule can be tuned by modification of its molecular structure, which may provide valuable routes to construct new materials with excellent all-round properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorene and 9,9′‐spirobifluorene derivatives with tailor‐made optical and redox properties are being actively investigated as organic light‐emitting materials for optoelectronics and in electrogenerated chemiluminescence studies 2022…”
Section: Introductionmentioning
confidence: 99%